Pengembangan Sistem Informasi Layanan Masyarakat Berbasis Web Mobile Menggunakan Metode Waterfall - Nawang Padjar Pancarro; Ledy Elsera Astrianty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Public services in Padukuhan V Tirtonirmolo, Kasihan, Bantul have so far been carried out manually through a WhatsApp group, resulting in ineffective processes for handling complaints, disseminating activity information, and managing inventory and domicile letters, as well as poor structure and documentation. This study aims to design and develop a web-mobile–based community service information system capable of integrating all administrative processes in the padukuhan digitally, quickly, accurately, and transparently. The research methods used include field observations, interviews with local officials, literature studies, and needs analysis to ensure that the system aligns with user context. The system development follows the Waterfall method through the stages of analysis, design, implementation, testing, and maintenance. The community application was built using Flutter, while the admin dashboard was developed using React.js, supported by a Node.js backend and a MySQL database. Testing was carried out using Black Box Testing across 14 test scenarios, all of which produced outputs that met the expected results. Additionally, non-functional testing using the System Usability Scale (SUS) with 10 respondents produced an average score of 84.5, categorized as Good to Excellent, indicating that the system is easy to use and provides a positive user experience. Based on these results, the information system effectively replaces manual processes with an integrated digital service that improves efficiency, quality, and accessibility of public services in Padukuhan V Tirtonirmolo.